The glocalisation of English-medium instruction examined through of the ROAD-MAPPING framework: A case study of teachers and students in a Vietnamese university. (August 2022) - Vo, Tho Doan; Gleeson, Margaret; Starkey, Louise
Abstract: English-medium instruction (EMI) is a growing phenomenon in Vietnamese higher education in response to globalisation and internationalisation. This paper examines how four subject teachers and their students in undergraduate economics-related EMI courses experienced the introduction of EMI. Data were gathered from interviews, classroom observation and focus group interviews and the findings were thematically analysed using the dimensions of the ROAD-MAPPING framework (Dafouz & Smit, 2016). The teachers and students found their expectations of the programme did not match the reality. In the process of glocalisation, the local was given insufficient focus in the largely imported curriculum and pedagogies. This suggests alignment is needed between top-down (international) policies and bottom-up (local) reality for EMI to work in practice.